Tucker, Llewellyn. Interview with Llewellyn Tucker of Elliston, NL about the Salvation Army Citadel in Elliston, NL. - Barrett, Terra (2016)
Interview with Llewellyn Tucker of Elliston, NL about the Salvation Army Citadel in Elliston, NL. Lewellyn James Tucker named after his uncle; Born in Bonavista on November 20, 1946; 00:58 - Going to the Salvation Army growing up; description of the inside of the church building; 2:45 – description of the Sergeant Major, Captains and Lieutenants; 4:15 – playing music; people on the platform; 5:57 – closure of the citadel; 7:12 – weddings, funerals; closure of the church; 10:35 – description of the services; 12:01 – description of the Salvation Army Barracks; 13:45 – renovations; 15:55 – thoughts on how the church should be used today; 16:25 – benches and chairs; Sunday school; instruments in the church; 20:12 – outdoor services; 21:18 – favourite memory of going to church; differences in the church when he was growing up compared to 2016; attending services with his cousins.